PERAN CUSTOMER RELATIONSHIP MARKETING TERHADAP NASABAH BANK SYARIAH INDONESIA - Adam Rakha Putra (2023)
The Customer Relationship Marketing Strategy is one of the bank's efforts to increase customer loyalty so that transactions at banking institutions do not stop and banks get income to continue to grow and expand. Bank Syariah Indonesia is a merging bank in 2021 between 3 Islamic banks, of course the role of Customer Relationship Marketing is needed which is able to make customers loyal to the bank. This study aims to determine how much BSI customer satisfaction with bank services. This research uses a quantitative method using a questionnaire on BSI customers, the results of the research show that BSI is good enough, but there are still deficiencies, namely ATM machines that are not spread in several places.